Receptor protein tyrosine phosphatase μ: Measuring where to stick - Radu Aricescu, A; Siebold, C; Yvonne Jones, E (2008)
We review here recent results on the structure and function of a receptor protein tyrosine phosphatase, RPTPμ. In addition to their intercellular catalytic domains which bear the phosphatase activity, the RPTPs are cell-surface-receptor-type molecules and in many cases have large extracellular regions. What role can these extracellular regions play in function? For RPTPμ, the extracellular region is known to mediate homophilic adhesion. Sequence analysis indicates that it comprises six domains: an N-terminal MAM (meprin/A5/μ), one immunoglobulin-like domain and four fibronectin type III (FN) repeats. We have determined the crystal structure of the entire extracellular region for RPTPμ in the form of a functional adhesion dimer. The physical characteristics and dimensions of the adhesion dimer suggest a mechanism by which the location of this phosphatase can be influenced by cell-cell spacings. © 2008 Biochemical Society.